Effects of reduced gluten intake through the inclusion of yellow pea-based products on abdominal symptoms in habitual wheat consumers: a non-randomized clinical trial - Hitoshi Shimbo; Mamoru Ito; Yuto Aoki; Joto Yoshimoto; Mikiya Kishi; Jiro Saito; Yukihiro Ohya; Masashi Nakamura; Senju Hashimoto; Akiko Yagami (European Journal of Nutrition, 2026)
Abstract Purpose Increasing attention has been paid to individuals who report gastrointestinal symptoms following wheat consumption. In addition to wheat allergy and celiac disease, non-celiac gluten sensitivity (NCGS) has been proposed as a clinical entity. Despite persistent symptoms, many affected individuals continue to consume wheat-containing foods. We aimed to investigate the impact of replacing wheat-based foods with gluten-reduced foods, specifically yellow pea pasta (YPP), bread (YPB), and chips (YPC), on the abdominal symptoms, quality of life (QOL), and gut microbiota in healthy individuals who habitually consume wheat frequently. Methods Thirty men and women aged 18–64 years with habitual high wheat intake were enrolled and divided into two groups based on the presence or absence of abdominal symptoms. Participants followed a 4-week gluten-reduced diet intervention using YPP, YPB, and YPC. Abdominal symptoms, QOL, gut microbiota, and selected blood biomarkers were evaluated before and after the intervention. Results The intervention led to significant improvement in abdominal distension, abdominal pain or discomfort, feeling of incomplete evacuation , hard stools, and urgent need for defecation. Baseline QOL differences between groups were no longer evident. Analysis of gut microbiota revealed maintenance and/or an increase in short-chain fatty acid-producing bacteria, with significant correlations observed between specific bacterial shifts and symptom improvement. Conclusions Yellow pea–based products (YPP, YPB, and YPC) may represent a promising dietary strategy for alleviating abdominal symptoms in individuals with high wheat consumption. This study was registered in the UMIN Clinical Trials Registry (UMIN Trial ID: UMIN000056466).